Breaching the Barrier: Investigating Initial Herpes Simplex Viral Infection and Spread in Human Skin and Mucosa - Hafsa Rana; Naomi R. Truong; Dona R. Sirimanne; Anthony L. Cunningham (Viruses)
Herpes simplex virus (HSV) is sexually transmitted via the anogenital mucosa where it initially infects epidermal keratinocytes and mononuclear phagocytes (MNPs). It then spreads to the dorsal root ganglion via sensory nerve endings, to remain latent for life with periodic reactivation. Currently, there is no cure or vaccine. Initial or recurrent HSV infection can produce serious complications and mediate acquisition of HIV. This review outlines the initial events after the HSV infection of human anogenital mucosa to determine the optimal window to target the virus before it becomes latent. After infection, HSV spreads rapidly within the mid-layers of epidermal keratinocytes in the explanted human inner foreskin. Infected cells produce chemokines, which modulate nectin-1 distribution on the surface of adjacent keratinocytes, facilitating viral spread. Epidermal Langerhans cells and dendritic cells become infected with HSV followed by a “viral relay” to dermal MNPs, which then present viral antigen to T cells in the dermis or lymph nodes. These data indicate the need for interruption of spread within 24 h by diffusible vaccine-induced mediators such as antiviral cytokines from resident immune cells or antibodies. Intradermal/mucosal vaccines would need to target the relevant dermal MNPs to induce HSV-specific CD4+ and CD8+ T cells.